POLA KOMUNIKASI POLITIK SALMIAH RAMBE DALAM MEMPERTAHANKAN ELEKTABILITAS MENUJU PEMILU 2024 (KOMUNIKA BANGSA, 2023)
Salmiah Rambe, as a member of the Bandung City Regional Representative Council (DPRD Kota Bandung), has held a position in Commission D for two terms beginning in 2014. She has a personal responsibility in maintaining her high level of electability in the previous 2019 elections. Salmiah's vote count in the 2019 elections increased almost threefold compared to the 2014 elections. In 2014, she received 4,219 votes, while in 2019 she received 11,074 votes. This is quite surprising considering her last name suggests a different cultural background than the area she is assigned to represent. The high level of electability needs to be maintained because it represents a trust given by the community and also indicates Salmiah's ambition to participate in the next 2024 elections. This research aims to determine the political communication pattern used by Salmiah Rambe in maintaining her electability towards the 2024 elections, and how this political communication pattern can help her.This study uses a qualitative descriptive approach.Â  The results of the data from the field show that Salmiah uses a circular political communication pattern, as proposed by Scharm and Osgood, which aligns with the political communication model developed by Dan Nimmo. Salmiah uses this communication pattern in every activity that allows her to meet with the community. It helps her understand the concerns and complaints of the community/constituents, so she can respond to these complaints with appropriate policies and assistance needed by the community/constituents. These policies and assistance bring benefits that are perceived by the community/constituents, which ultimately influence the trust of the community/constituents and affect Salmiah Rambe's level of electability.Keywords: Political Communication, Salmiah Rambe, Electability.